Pengaruh Kualitas Pelayanan, Citra Perusahaan dan Lokasi terhadap Kepuasan Nasabah di PT. Taspen (Persero) Cabang Surakarta - Eny Kustiyah; Istiqomah Dwi Astuti; Supawi Pawenang (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to analyze the influence of service quality, company image and location, simultaneously and partially on customer satisfaction in TASPEN (Persero) company of Surakarta. Determination of the sample using purposive sampling technique to sample as many as 100 people. Technique of collecting data in this study use questionnaires. Technical of analyzing used multiple linear regression, F test, t test, the coefficient of determination. The results of the analysis showed the quality of service, corporate image and the location, simultaneously and partially have positive effect and significant impact on customer satisfaction in TASPEN (Persero) company of Surakarta.